The Correlation between Frequency and Motivation in Peer Assisted Learning to OSCE Scores on Medical Students - Nurcahyo, Daniel Satyo; Subandono, Jarot; Wijayanti, Lilik (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Peer Assisted Learning (PAL) was one of learning methods that helped in the learning of clinical skills. There was some medical students that needed more PAL than other medical students and also participantsâs motivation in PAL was different each other. This research meant to analyze the effect of frequency and motivation in Peer Assisted Learning to Objective Structured Clinical Examination (OSCE) Score. Methods: This research was an observational analytic using cross sectional method, which held on 2014 on first year medical students of Fakultas Kedokteran Universitas Sebelas Maret. Sampling method was using total population sampling, with inclusion and exclusion criteria. Data measured with questionarre. From questionarre gained 117 data and analyzed using Spearman test. Results: This research showed significant effect of frequency and motivation in Peer Assisted Learning to Objective Structured Clinical Examination (OSCE) Score. The Spearman test was resulted pfrekuensi = 0.002 and pmotivasi = 0.006 (<0.05). Conclusions: There is significant effect from frequency and motivation in Peer Assisted Learning in OSCE Score. Keywords: Peer assisted learning, skills lab, Objective Structured Clinical Examination.Â